Intercropping of castor bean and sugarcane under irrigation: part 2: yield and agronomic indices - Alexandria Júnior, Francisco Figueiredo de; Alves, Everton JohnCamelo; da Silva, Silvanete Severino; Dantas Neto, José; Azevedo, Carlos Alberto Vieira de (Comunicata Scientiae, 2019)
Intercropping can be an alternative to maximize yields of castor bean and sugarcane. This work aimed to investigate the yields and agronomic indices of castor bean and sugarcane in intercropping system. The experiment was carried out in the field, at the Ponta da Serra Farm, in the municipality of Queimadas-PB, Brazil. Treatments resulted from a 4 x 4 factorial arrangement, with twelve replicates. The irrigation depths (drip system) tested were: 50, 75, 100 and 125% crop evapotranspiration, and the spacings used for castor bean were: (1 x 0.5 m), (1 x 1 m), (1 x 1.5 m) and (1 x 2 m), that is, 20,000, 10,000, 6,666 and 5,000 plants per hectare, respectively, with total area of 2,880 m², each one with twelve plots of castor bean spacing. The following variables were evaluated: land equivalent ratio and relative crowding coefficient. For all irrigation depths tested, sugarcane yield increased linearly with the increment in castor bean spacing. The highest value of land equivalent ratio was found at 1 x 0.5 m spacing, and the lowest values of relative crowding coefficient for sugarcane occurred at 1x 0.5 m spacing for all irrigation depths.